(untitled) (Contemporary Journal of Social Science Review, 2025)
Two-dimensional (2D) nanocomposite materials have emerged as highly promising electrode candidates for next-generation supercapacitors due to their exceptional surface activity, tunable interlayer spacing, and superior charge transport pathways. However, their electrochemical performance is not solely governed by intrinsic material chemistry; rather, it is critically shaped by external processing parameters, particularly temperature, precursor/electrolyte concentration, and synthesis methodology. This study presents a performance-oriented critical analysis of how these key variables regulate the structural evolution, interfacial engineering, and charge-storage mechanisms of 2D nanocomposite electrodes for supercapacitor systems. The analysis highlights that temperature-dependent phase stabilization, defect modulation, and annealing-driven conductivity enhancement strongly influence charge-transfer resistance and cycling durability. Likewise, concentration-controlled nucleation and growth kinetics determine nanosheet thickness, porosity distribution, and the accessibility of electrolyte ions, thereby directly impacting capacitance behavior and rate capability. Furthermore, synthesis-route selection—including hydrothermal, solvothermal, chemical vapor deposition, electrodeposition, and sol–gel strategies—significantly governs layer stacking, dispersion uniformity, and oxidation resistance, leading to distinct electrochemical profiles in terms of energy density, power density, and coulombic efficiency. The integrated evaluation demonstrates that the synergy of these parameters determines the dominance of EDLC, pseudocapacitive, or hybrid charge-storage mechanisms, ultimately defining the real-world applicability of 2D nanocomposite supercapacitor electrodes. The study concludes that future optimization should prioritize scalable synthesis, stability-oriented defect regulation, and intelligent parameter tuning frameworks to achieve high-performance, durable, and commercially viable supercapacitor devices.